THE INFLUENCE OF SKIPPING EXERCISES ON SMASH JUMP PERFORMANCE IN GRADE VIII STUDENTS OF SMP NEGERI 1 LAUBALENG - Muhamad Azlan Karo-Karo; Orbit Irwansyah; Melfa Br Nababan (RADJA PUBLIKA, 2025)
This study aims to empirically investigate the effect of a structured skipping exercise program on the smash jump performance of eighth-grade students at SMP Negeri 1 Laubaleng. The research employed a quantitative experimental method, utilizing a one-group pretest-posttest design to isolate and measure the impact of the intervention. A sample of 32 students was selected through total sampling techniques, ensuring the participation of an entire class cohort. The primary instrument for data collection was the standardized badminton smash accuracy test, as endorsed by the Indonesian Badminton Association (PB PBSI), which assesses both the power and precision of the smash shot. The experimental intervention consisted of a 6-week skipping training program, administered three times per week for 45 minutes per session. Each session was carefully structured to include a warm-up, a core skipping component involving various techniques (two-foot jump, alternate foot, speed variations), and a cool-down period. The collected data were subjected to rigorous statistical analysis, including tests for normality and homogeneity, followed by a paired t-test to determine the significance of the observed changes. The results demonstrated a substantial and statistically significant improvement in smash performance, with the mean score increasing from 29.44 (SD = 5.073) in the pretest to 50.5 (SD = 5.663) in the posttest. The t-test analysis confirmed a significant effect (p < 0.05), leading to the conclusion that the skipping exercise program was highly effective in enhancing the students' smash jump ability. These findings strongly recommend the integration of skipping as a viable, efficient, and cost-effective alternative training methodology within badminton instruction and physical education curricula, particularly for developing the foundational physical qualities required for powerful offensive shots.